Prenatal Management Strategy for Immune-Associated Congenital Heart Block in Fetuses - Liao, Hongyu; Tang, Changqing; Qiao, Lina; Zhou, Kaiyu; Hua, Yimin; Wang, Chuan; Li, Yifei (Frontiers in Cardiovascular Medicine, 2021)
Fetal congenital heart block (CHB) is the most commonly observed type of fetal bradycardia, and is potentially life-threatening. More than 50% of cases of bradycardia are associated with maternal autoimmunity, and these are collectively termed immune-associated bradycardia. Several methods have been used to achieve reliable prenatal diagnoses of CHB. Emerging data and opinions on pathogenesis, prenatal diagnosis, fetal intervention, and the prognosis of fetal immune-associated CHB provide clues for generating a practical protocol for clinical management. The prognosis of fetal immune-associated bradycardia is based on the severity of heart blocks. Morbidity and mortality can occur in severe cases, thus hieratical management is essential in such cases. In this review, we mainly focus on optimal strategies pertaining to autoimmune antibodies related to CHB, although the approaches for managing autoimmune-mediated CHB are still controversial, particularly with regard to whether fetuses benefit from transplacental medication administration. To date there is still no accessible clinical strategy for autoimmune-mediated CHB. This review first discusses integrated prenatal management strategies for the condition. It then provides some advice for clinicians involved in management of fetal cardiovascular disorder.